ANALISIS PENERAPAN METODE STORYTELLING OLEH ORANG TUA DALAM PENGEMBANGAN BAHASA ANAK USIA DINI PADA PENDIDIKAN NONFORMAL DI LINGKUNGAN KELUARGA - Serasi Zendrato; Fira Aprilia; Ayu Siregar; Maria Benedicta Florenta Tamba; Jubaidah Hasibuan; Fauzi Kurniawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Language development is an important aspect of early childhood growth because it is closely related to children's communication skills, thinking abilities, and social interactions. The family environment, as a form of nonformal education, plays a crucial role in providing language stimulatio1n for children, one of which is through storytelling activities. This study aims to analyze the implementation of the storytelling method by parents in developing early childhood language skills within the family environment. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of two parents who have children aged 4-6 years and actively conduct storytelling activities at home. The study was conducted on Tuasan Street, Sidorejo Hilir, Medan Tembung District, Medan City. Data collection techniques included observation, semi-structured interviews, and documentation. The results of the study indicate that regularly conducted storytelling activities can increase children's involvement in communication processes, enrich vocabulary, and build children's confidence in expressing their opinions. The use of media such as illustrated storybooks and storytelling delivered with expressive gestures and engaging intonation also enhances children's attention during the activity. Although there are challenges such as limited time and limited variations of storytelling media, storytelling remains a simple and effective method to support early childhood language development within the family environment.